Mind your heart: Healthy heart for hearty health - V Chockalingam; Anand Chockalingam; Priya Chockalingam (Journal of Clinical and Preventive Cardiology, 2017)
The incidence and prevalence of cardiovascular disease (CVD) are burgeoning in many countries, including India. Lifestyle management and the use of appropriate preventive therapies are keys to halting this rapidly growing public health problem. Importantly, the role of psychosocial stress in causation of CVD is now being increasingly recognized. It is important to recognize the positive aspects of life and suppress the negative personality traits to achieve long-term happiness and physical health, free from CVD.